Microbubbles traversing the blood-brain barrier for imaging and therapy - Meairs, Stephen; Alonso, Angelika; Fatar, Marc; Kern, Rolf; Hennerici, Michael G. (Medical & biological engineering & computing, 2009)
In the last several years great progress has been made in the field of ultrasound perfusion imaging of the brain. Different approaches have been assessed and shown to be capable of early detection of cerebral perfusion deficits. Real-time low mechanical index imaging simplifies the acquisition of perfusion parameters and alleviates many of the previous imaging problems related to shadowing, uniplanar analysis, and temporal resolution. With the advent of this new, highly sensitive contrast-specific imaging technique new possibilities of real-time visualization of brain infarctions and cerebral hemorrhages have emerged. Microbubbles that traverse the blood-brain barrier (BBB) can also elicit bioeffects that may be used to open the BBB for targeted delivery of macromolecular agents to the brain. Possible ways in which substances cross the BBB after application of this novel approach include transcytosis, passage through endothelial cell cytoplasmic openings, opening of tight junctions, and free passage through injured endothelium. Although relatively little tissue damage occurs at low acoustic intensities capable of opening the BBB, no investigation has demonstrated a total lack of BBB injury when using ultrasound and microbubbles. Further studies are necessary to address the effects of ultrasound and microbubbles upon the various transport mechanisms of the BBB. Moreover, investigations aimed at elucidating how ultrasound and microbubbles interact at the molecular level of the BBB are necessary. Results of such studies will increase our understanding of the mechanisms of BBB opening and also allow a better appraisal of the safety of this technique for future clinical applications.
Gesehen am 17.03.2021